The Effect of Environmental, Social, and Governance (ESG) Disclosure on Financial Performance in the Consumer Cyclical Sector (Listed on the Indonesia Stock Exchange for Period 2020-2023) - Puspitasari, Arum Diah; Maryani, Neni (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research primarily investigates how the disclosure of environmental, social, and governance (ESG) aspects influences the financial performance of companies listed on the Indonesia Stock Exchange (IDX) during the period of 2020 to 2023. This research employs a quantitative approach, utilizing secondary data obtained from the official website of the IDX, specifically from the cyclical consumer sector. A purposive sampling method was used to select 16 cyclical consumer companies out of 164 listed on the IDX over four years, resulting in a dataset of 64 observations. Data analysis techniques, including classical assumption tests, multiple linear regression, t-tests, and F-tests, were performed using SPSS Version 29. The findings indicate that, partially, environmental disclosure significantly affects financial performance, whereas social and governance disclosures do not. Simultaneously, the combined disclosures of environmental, social, and governance aspects do not significantly influence financial performance.